Implementasi Problem Based Learning dengan Media Digital Transberi pada Pemahaman Konsep IPAS Siswa Kelas IV - Yuniza Amalia Noor; Sekar Dwi Ardianti; Yuni Ratnasari (JANACITTA, 2025)
Abstract This study aims to assess the effectiveness of the Problem Based Learning (PBL) model with the help of Transberi media in improving the understanding of science concepts in fourth-grade students. Inappropriate use of learning models and media has the potential to reduce conceptual understanding and student participation, as seen from the results of the pre-study which showed that many students obtained below average scores. Application in this context refers to the extent to which a learning medium successfully achieves its intended objectives. The PBL model is an approach that emphasizes problem-solving as a means to foster in-depth conceptual understanding. Transberi media is designed as a fun, interactive tool to facilitate students' understanding and retrieval of learned concepts. Conceptual understanding itself is defined as a student's ability to re-present specific knowledge in a more general form for easier comprehension. This study used a quantitative method with a one-group pre-test post-test pre-experimental design. The research sample was all fourth-grade students of SD 02 Bategede. Data collection techniques included interviews, observations, tests (pre-test and post-test), and documentation. Data were analyzed using normality tests, and n-gain tests.The results of the N-Gain score analysis in this study showed an average of 0.5568, which is included in the moderate category (0.30 ≤ g < 0.70). This indicates an increase in students' understanding of science concepts by 55.68% after the implementation of the Problem-Based Learning learning model supported by Transberi media. This finding is consistent with the results of previous studies, which confirmed the effectiveness of the PBL model in improving conceptual understanding, especially in fourth-grade elementary school students. Abstrak Penelitian ini bertujuan untuk mengkaji efektivitas penerapan model Problem Based Learning (PBL) berbantuan media Transberi dalam meningkatkan pemahaman konsep IPAS pada siswa kelas IV. Ketidaktepatan penggunaan model dan media pembelajaran berpotensi menurunkan pemahaman konsep dan partisipasi siswa, sebagaimana terlihat dari hasil pra-penelitian yang menunjukkan banyak siswa memperoleh nilai di bawah rata-rata. Penerapan dalam konteks ini merujuk pada sejauh mana suatu media pembelajaran berhasil mencapai tujuan yang diharapkan. Model PBL merupakan pendekatan yang menitikberatkan pada pemecahan masalah sebagai sarana untuk mendorong pemahaman konsep secara mendalam. Media Transberi dirancang sebagai alat bantu interaktif yang menyenangkan untuk mempermudah siswa memahami dan menyampaikan kembali konsep yang dipelajari. Pemahaman konsep sendiri diartikan sebagai kemampuan siswa dalam merepresentasikan kembali suatu ilmu secara spesifik ke dalam bentuk yang lebih umum agar lebih mudah dipahami. Penelitian ini menggunakan metode kuantitatif dengan desain pre-eksperimental tipe one-group pre-test post-test. Sampel penelitian adalah seluruh siswa kelas IV SD 02 Bategede. Teknik pengumpulan data meliputi wawancara, observasi, tes (pre-test dan post-test), serta dokumentasi. Data dianalisis melalui uji normalitas, dan uji n-gain. Adapun hasil analisis skor N-Gain dalam penelitian ini menunjukkan rata-rata sebesar 0,5568, yang termasuk dalam kategori sedang (0,30 ≤ g < 0,70). Hal ini mengindikasikan adanya peningkatan pemahaman konsep IPAS siswa sebesar 55,68% setelah penerapan model pembelajaran Problem-Based Learning yang didukung oleh media Transberi. Temuan ini konsisten dengan hasil penelitian sebelumnya, yang menegaskan efektivitas model PBL dalam meningkatkan pemahaman konsep, khususnya pada siswa kelas IV sekolah dasar.